Maximum number of embryos to be transferred in assisted reproductive technologies cycle: Ethics opinion - Madhuri Patil; Duru Shah (Wolters Kluwer Medknow Publications, 2018)
Prevention of multiple pregnancies is of utmost importance as with multiple pregnancy-assisted reproductive technologies results shifts from success to complications. There is an increase in the maternal and neonatal morbidity and mortality with occurrence of higher order pregnancies. Therefore, restricting the number of embryos transferred either to one or two would reduce the occurrence of multiple pregnancy.